Influence of caffeine on crystallization and amelioration of oxidative stress on in vitro model of urolithiasis - Ninčević, Vjera (Array, 2020)
Urolithiasis is a disease characterized by formation of solid crystals within the urinary tract. Kidney stone formation is still not clear but it is mostly composed of calcium oxalate which can produce free radicals that are toxic to renal tubular cells. Oxidative stress is an important contributory mechanism in cell damage and is associated with a number of disorders. Several studies have shown antioxidative effects of caffeine, proposing its possible role in stopping the formation of calcium oxalate stones in urinary tract. Hence, the aim of this study was to evaluate the toxic effects of calcium oxalate monohydrate crystals (COM) on renal epithelial cell line; Madin-Darby canine kidney cells subtype I (MDCK I) and Epithelial-like pig kidney cell line (LLC-PK1), and to determine possible inhibition of COM that caused oxidative stress by antioxidant treatment with caffeine in different concentrations in a cell culture model of urolithiasis.